A new species of the genus Aeschnosoma selys, 1870 (Odonata: Anisoptera: Corduliidae s.s.) - Fleck, Günther; Neiss, Ulisses Gaspar (Zootaxa, 2012)
The larva, the adult male and the adult female of Aeschnosoma hamadae sp. nov. are described and illustrated. This species belongs to the A. elegans group of species. A comparison with other species of this group is given. Copyright © 2012, Magnolia Press.
Keywords: Aeschnosoma; Aeschnosoma Elegans; Aeschnosoma Marizae; Anisoptera (dragonflies); Corduliidae; Odonata